Application of Membrane Technology to Slaughterhouse Blood to Produce Edible Powdered Protein Mixture - Kokkora, Maria I.; Petrotos, Konstantinos B.; Gkoutsidis, Paschalis E.; Mpoulmpos, Christos (Journal of Membrane and Separation Technology, 2012)
Animal blood generated from slaughtered animals is often released into the environment resulting in significant pollution and also in the loss of a valuable protein source. This study aimed at developing a procedure that will allow for utilizing animal blood for protein powders production on an industrial scale. To meet this goal, hygienically collected animal blood was first treated with membrane technology: microfiltration (MF) or ultrafiltration (UF). A ceramic MF membrane and a PCI UF membrane were used. Average MF flux was 6.62 kg h-1 m-2 at transmembrane pressure of 2.5 bar. Average UF flux was 3.55 kg h-1 m-2 at transmembrane pressure of 4 bar. MF succeeded in separating the blood plasma proteins (permeate) from the red cell fraction (retentate). UF concentrated both the red cell and blood plasma proteins in a single sample (retentate). The volume ratio of retentate to permeate was 10:14 and 14:10, for the MF and UF, respectively. A membrane cleaning regime was developed. The treated blood fractions were then freeze dried and red and white protein powders were produced successfully. The potential of a SME (small-medium enterprise) to apply this procedure into practice is presented.